BARRIERS TO MALE INVOLVEMENT IN ANTENATAL CARE IN UGANDA. A SYSTEMATIC LITERATURE REVIEW. - TUMWINE , ANDREW; KIRUMIRA, JIMMY (Student’s Journal of Health Research Africa, 2025)
Background Globally, men are significant figures in the decision-making processes of the family, especially to their expectant partner. During this period, mothers, their unborn babies, family members, and more so their husbands are excessively worried. This study aimed to assess the barriers to male involvement in ANC services in Uganda. Methods. A systematic review of journal articles was carried out using the search words “Barriers”, “Male involvement,” and “Antenatal Care”. Different medical databases, such as Google Scholar, Research Gate, and PubMed, were used. A total of 134 relevant articles were published between 2010 and 2020 but were reduced to 36 most relevant full-text articles, of which 20 were Ugandan studies hinting at male involvement in Antenatal Care (ANC) services. Findings. The review revealed that barriers to male involvement in ANC services in Uganda were classified as gender and cultural norms, lack of services targeting male partners, poor ANC service delivery, free availability of TBAs, poverty, long distances to ANC clinics and long waiting time at health centers, fear of HIV/AIDs testing and lack of specific services targeting men. Conclusion. There are many barriers to male involvement in ANC services in Uganda. Husbands are vital in the lives of pregnant mothers; thus, attending to these barriers could significantly increase male involvement in ANC services. Recommendations. The government of Uganda should involve community extension workers in sensitizing households on the benefits of husband involvement in ANC as well as improving service delivery and health care centers.